2016 IEEE Conference on Computational Intelligence and Games (CIG) 2016
DOI: 10.1109/cig.2016.7860404
|View full text |Cite
|
Sign up to set email alerts
|

Platformer level design for player believability

Abstract: Abstract-Player believability is often defined as the ability of a game playing character to convince an observer that it is being controlled by a human. The agent's behavior is often assumed to be the main contributor to the character's believability. In this paper we reframe this core assumption and instead focus on the impact of the game environment and aspects of game design (such as level design) on the believability of the game character. To investigate the relationship between game content and believabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Besides the presented works, there are other ways to create players' models and personalize game content. For instance, Camilleri, Yannakakis, and Dingli [8] crowdsourced rank-based annotations from users watching videos of characters controlled by AI and humans playing a 2D platform game to model believability, i.e., the ability to convince observers that a human player is controlling a character. Blom et al [7] personalized levels of Infinite Mario Bros [45] according to players' facial expressions, i.e., during the gameplay, the experience adapted to the players' emotions inferred from the facial expression recognition.…”
Section: Player Modelingmentioning
confidence: 99%
“…Besides the presented works, there are other ways to create players' models and personalize game content. For instance, Camilleri, Yannakakis, and Dingli [8] crowdsourced rank-based annotations from users watching videos of characters controlled by AI and humans playing a 2D platform game to model believability, i.e., the ability to convince observers that a human player is controlling a character. Blom et al [7] personalized levels of Infinite Mario Bros [45] according to players' facial expressions, i.e., during the gameplay, the experience adapted to the players' emotions inferred from the facial expression recognition.…”
Section: Player Modelingmentioning
confidence: 99%
“…In [3] an experiment was carried out in which two players and two computers with artificial intelligence play a platform game similar to "Infinite Mario Bros" (a platform game). The following parameters were selected to determine the effectiveness of the players' gameplay: completion time, last life game play duration, percentage of time spent running left, percentage of time spent running, number of jumps, number of unsuccessful jumps, number of collected coins, number of kicked shells, number of deaths caused by falling into a hole, number of deaths caused by enemies, number of killed enemies, number of enemies killed by a kicked shell.…”
Section: Literature Overview On Software Preparationmentioning
confidence: 99%
“…Finding normative protocols for believability assessment is important; while the common belief is that an agent's believability depends only on the AI that controls it [32], this is far from being true. In particular, Camilleri et al showed that changing an agent's environment affects their perceived believability levels [33]. In their study the authors asked players to annotate the believability of a platform game play-through.…”
Section: Believability Evaluationmentioning
confidence: 99%